TRAINING OF IN-DEMAND ENGINEERS FOR OIL-AND-GAS COMPLEX - Aleksei F. Ivanov (Высшее образование в России)
The article discusses the features of professional training system for oil and gas complex based on the integration of education, science and industry. This system is intended to foster practice-oriented education of professionals and generally to improve the quality of training. The article dwells on the interaction areas between the Oil Institute and the enterprises, the forms of employer's participation in educational process and in curricular formation. The advanced learning is provided by the research-and-education centre with laboratories equipped with world class equipment and facilities based on the latest technologies.